CRITICAL VARIABLES OF MORPHO-PHYSIOLOGICAL RICE PLANT UNDER STAGNANT FLOODING CONDITIONS - Nurwulan Agustiani; Sujinah Sujinah; Indrastuti Apri Rumanti (Indonesian Journal of Agricultural Science, 2021)
Stagnant flooding (SF) stress has contributed decreasing rice production in Indonesia. The study aimed to explore critical variables of rice growth that contribute to the decreasing grain yield under SF conditions and a common irrigation system (control). The experiment was arranged in a complete randomized block design with four replications to test 10 rice genotypes (Inpari 30 Ciherang Sub-1, Inpara 3, Inpara 4, Inpara 8, IRRI119, IRRI154, IR42, IR14D121, IR14D157, and Tapus). The water depth was managed according to the farmer’s practices for control, while for SF plots the standing water depth was gradually increased from 35 days after transplanting and was maintained at 50 cm until harvest. Results showed that plant height, tillering ability, leaf greenness, panicle number per hill and grain filling percentage were critical growth variables that affect grain yield at optimal conditions. The yield of the 10 genotypes decreased by 25–50% under SF conditions. Inpara 3 had the stable yield in those two watering conditions. Therefore, it could be used as a check variety for SF condition. Inpara 9 and IRRI119 experienced decreased yield of more than 50% under SF conditions. The key factors determining the decreased yield were tillering ability and green leaf level. Optimization of the two variables at SF conditions will largely determine rice yield associated with panicle number per hill and grain number per panicle. Results of the study are useful as preliminary recommendations for designing new variety and cultivation techniques to reduce the impact of SF stress on rice yield.